Oleic acid increases uptake and decreases the P-gp-mediated efflux of the veterinary anthelmintic Ivermectin - Houshaymi, Bilal; Nasreddine, Nadine; Kedees, Mamdouh; Soayfane, Zeina (Drug Research, 2019)
The bioavailability of ivermectin is modulated by lipid-based formulations and membrane efflux transporters such as Breast Cancer Resistance Protein and P-glycoprotein (BCRP and P-gp). We have investigated the effect of oleic acid on the uptake of ivermectin in vitro using Caco-2 cells and in vivo in the intestines of wild-type mice. Complex micelles (M) with oleic acid induced a significant increase (e. g. for M3 was 7-fold, p≤0.001) in the uptake of the drug in a time-dependent manner with no involvement of cholesterol in the mechanism. In vivo results showed a significant increase in the concentration of plasma and intestinal mucosa ivermectin (p≤0.01) in mice receiving oleic acid-based drug formulation. We also examined the expression of the drug efflux transporter, BCRP and P-gp in Caco-2 cells and found a significant decrease (p≤0.001) in their level in the presence of 5 mM oleic acid. Treatment of mice with oleic acid-based formulation showed a significant decrease in the activity of P-gp in the intestinal mucosa (p≤0.01). This study highlighted the effect of oleic acid in decreasing the expression and the activity of P-gp-mediated ivermectin efflux and in limiting the drug absorption by increasing its uptake and bioavailability in Caco-2 cells and intestine, respectively.
Keywords: Oleic acid; ivermectin; P-glycoprotein; BCRP